The Influence of Online Media Exposure Behavior and Parception Image of T-pop Artists on Fans Club Participation - Boonwan, Tanatcha; Sasithanakornkaew, Saranthorn; Kumsubha, Bhanond (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to 1) compare differences between demographic characteristics and fan engagement in T-Pop activities, 2) examine the relationships between online media exposure behavior, perceived artist image, and fan engagement, and 3) investigate the influence of online media exposure behavior and perceived artist image on fan engagement. A quantitative research design was employed. The sample consisted of 400 T-Pop fans in Thailand, selected using non-probability convenience sampling. Data were collected through a structured questionnaire and analyzed using descriptive and inferential statistics. The results indicated that T-Pop fans exhibited high levels of online media exposure behavior (M = 4.06), perceived artist image (M = 4.43), and fan engagement (M = 3.81). The demographic difference analysis revealed that age, education level, income, and occupation significantly differed in terms of online media exposure behavior. Furthermore, online media exposure behavior and perceived artist image were found to be significantly correlated with fan engagement. The results of multiple regression analysis demonstrated that online media exposure behavior and perceived artist image.